Optimizing the Development of P5 Worksheets for Teachers: Shaping Student Character at SMAN 1 Terara, East Lombok Regency - Susilawati Susilawati; Aris Doyan; Ahmad Busyairi; Syahrial Ayub; Nina Nisrina (Unram Journal of Community Service, 2024)
Character education through the implementation of P5 (Projek Penguatan Profil Pelajar Pancasila) is an important initiative in the Indonesian education system to form students with integrity and national insight. This research aims to optimize the development of the P5 Worksheet for teachers at SMAN 1 Terara, East Lombok Regency, with a focus on building student character. Evaluation is carried out based on the responses of training participants regarding various aspects of material delivery and the abilities of the presenters. The results showed that the majority of participants (50) strongly agreed that the material was delivered well, while 15 participants agreed. The delivery of P5 integration was considered interesting by 44 participants who strongly agreed and 21 participants who agreed. The material was considered easy to understand by 48 participants who strongly agreed and 17 participants who agreed. Apart from that, the presenters were considered capable of creating creativity in the participants, with 47 participants strongly agreeing and 18 participants agreeing. There were no participants who gave responses that disagreed or disagreed with all aspects assessed. Overall, the results of this research show that the development of the P5 Worksheet is effective in improving the quality of learning and shaping student character in accordance with the Pancasila Student Profile